Safety and Effectiveness of Endoscopist-Directed Nurse-Administered Sedation during Gastric Endoscopic Submucosal Dissection - Yong Suk Cho; Sang youn Shin; Changhyeok Hwang; Jeonghun Seo; Jong Won Choi; Byung Kyu Park; Sun Young Won; Chun Kyon Lee; Yong Kang Lee; Han Ho Jeon (Gastroenterology Research and Practice)
Background and Aims. Endoscopic submucosal dissection (ESD) is routinely performed in treating gastric neoplasia and requires long-term higher levels of sedation. Endoscopist-directed nurse-administered sedation (EDNAS) has not been well studied in ESD. This study aimed to evaluate the safety and effectiveness of EDNAS for ESD. Methods. Patients treated with ESD for gastric tumors between 2013 and 2015 were retrospectively collected. Patients were divided into a midazolam-treated group (M group) and a midazolam plus propofol-treated group (MP group). Clinical outcome, safety, effectiveness, adverse events of ESD, and adverse events of sedation were analyzed. Results. Of 209 collected patients, 83 were in the M group and 126 were in the MP group. Of all patients, 67 patients had the circulatory adverse event during the ESD procedure. Sedation method was the only significant risk factor (M versus MP: 2.17 (1.14–4.15), p=0.019). In analysis of MP subgroups, 47 patients suffered an adverse event from sedation, and current smoking was the only significant association factor for adverse event (0.15 (0.03–0.68), p=0.014). Conclusions. In performing ESD, the effect of sedation is reduced in smoking patients. EDNAS may be acceptable for ESD under careful monitoring of vital sign and oxygen saturation.